The importance of sustainability in public transport / Muhamad Aiman Afiq Mohd Noor... [et al.] - Mohd Noor, Muhamad Aiman Afiq; Anuar, Ahmad Faiz; Isnain, Abdul Hakim; Abd Rahman, Muhd Nur Alif; Mohamad Farid, Mohamad Farhan; Azman, Mohd Asyraf (Universiti Teknologi MARA, Kedah, 2018)
Public transportation is a shared passenger transport service provided to transit people which is available for public usage. Public transport also is one of the solution to the sustainability system. Environmental issues become the main topic on these days and one of the causes is emission from a vehicle. The purpose of this study is to understand the principles, problems. and approaches of discipline on sustainability in public transportation. The objectives of the research are to identify what is sustainability transportation impacts on environmental, to analyses the importance of public transport in terms of sustamabihty. and to determine the existing approaches from different discipline for attract people to use public transport. The qualitative interview was used to get primary data and data collection as a secondary data used for gather the information from journals. articles, news, and website. The research is focused on bus and scope at Lembah valley area in Malaysia. The research have found the opportunity of using public transport that become major role in sustainability system in Malaysia.